The Essence of the Open Proportional System in the 2024 General Election in Central Java (Perspective of Law Number 7 of 2017) - Kadir, La Ode Ibrah Haikal Rachman; Rodiyah, Rodiyah; Damayanti, Ratih (Faculty of Law, Universitas Negeri Semarang, 2025)
One of the main instruments for implementing democracy in Indonesia is the General Election (Pemilu), which serves to elect the President, the House of Representatives (DPR), the Regional Representative Council (DPD), and the Regional House of Representatives (DPRD). To elect members of the DPR, DPD, and DPRD, Indonesia adopts an open-list proportional representation system where candidates are elected based on the highest number of votes. This system offers significant advantages by ensuring more accurate political representation and proportional seat distribution, thereby valuing each vote. This article focuses on critically examining the application of the open-list proportional system in the 2024 DPRD election in Central Java. The research method used is a socio-legal approach with qualitative analysis, emphasizing the implementation of open proportionality in the second-level DPRD elections in Central Java. The findings reveal legal uncertainty in the Election Law, particularly in Article 426, which contains structural loopholes that undermine the core principles of open proportional representation and potentially harm the essence of democracy itself. This issue was evident in the 2024 DPRD election in Central Java, where manipulation of the people's choice through resignation or dismissal from party membership, along with formalistic judicial decisions, created a legal gap that was exploited to disregard legitimate votes. This not only invalidates the legitimacy of individual representatives but also raises serious questions about who truly holds sovereignty in determining the composition of the legislature.